INTERAKSI TANGGUNG JAWAB SOSIAL, KINERJA SOSIAL, KINERJA KEUANGAN DAN LUAS PENGUNGKAPAN SOSIAL (Uji Motif di Balik Social Responsibility Perusahaan Go publik di Indonesia) - Nor Hadi (Universitas Muhammadiyah Semarang, 2011)
AbstractThe research investigated is reciprocal relationship two motives responsibility are social motive and economics motive. The variable of the research are cost social performance, economics performance and social disclosure, the have reciprocal relationship. Grand theory of the research is stakeholder and legitimacy theory.The objective of this research are b investigate direct effect and reciprocal effect of research variables. The Result from study show that different level of social disclosure The resulted of hipotetico testing, indicate (l) direct effect of social cost on social performance (H1) and social cost on social disclosure (H4) are significant (a = 0.100). (2) The reciprocal affect of differential stock price on social disclosure (H6C) social performance on return on equity (H5) and social performance on return on assets (H5) are significant (α=0.100) Based on content analysis in annual report and hipotetic testing indicate motive content on (social motive and economics motive) in social responsibility are existed. The motive content are effective, will be contingent. There are (reciptocal) relationship. The firm should be based on community excess concept in social responsibility practice.Keyword : Corporate Social Responsibility, Social Cost, Social Disclosure, Social performance, Financial Performance",